Pengaruh Online Costumer Review, Harga dan Kualitas Produk terhadap Keputusan Pembelian Kopi Gayo Arabika Melalui Market Place : (Studi pada Masyarakat Kota Banda Aceh) - Ari Arsadi; Zulkifli Umar; Mirza Murni (Jurnal Sains dan Ilmu Terapan, 2025)
This study aims to analyze the influence of Online Customer Reviews, price, and product quality on the purchasing decisions of Gayo Arabica coffee through online marketplaces, with a case study on the residents of Banda Aceh City. The research is motivated by the growing use of digital platforms, which has shifted consumer behavior from traditional to online purchasing. Data were collected through questionnaires distributed to 96 respondents, selected using a non-probability sampling technique with an accidental sampling approach. The results show that partially, Online Customer Reviews, price, and product quality each have a significant influence on purchasing decisions. Specifically, Online Customer Reviews significantly affect consumer trust, price sensitivity, and product perception. Furthermore, product quality plays a crucial role in determining customer satisfaction and loyalty. Simultaneously, these three variables also significantly affect consumer purchasing decisions when combined. These findings imply that Gayo Arabica coffee business actors should pay attention to customer reviews, apply competitive pricing, and maintain product quality to enhance online purchasing decisions.